Filipino-English bilingual speech recognition system - Campos, Diane Kristine M. (2004)
It is not unusual for a Filipino to switch between the English and Filipino language within a sentence. Thus it is important to develop a speech recognizer that can recognize both English and Filipino speech. In this project we developed a word-level bilingual speech recognition system which can recognize Filipino and English language. The speech data used was composed of the DARPA TIMIT Acoustic-Phonetic Continuous Speech Corpus, APPLE Continuous English Speech Corpus and the Filipino Speech Corpus being developed at the DSP laboratory. Also, software tools from the International Computer Science Institute, MatLab, and results of past projects of the DSP Speech Group were used to achieve the desired output of this project. The bilingual speech recognition system had a unique bilingual phoneme set, dictionary, acoustic model and language model. The bilingual phoneme set mapped both English and Filipino phones. The bilingual lexicon was a superset of the words from both languages. The Hidden Markov model was used to build the acoustic model trained from the speech data. The bilingual language model's n-gram statistics was obtained from sentences composed of Filipino words and sentences composed of English words. The bilingual lexicon, bilingual acoustic model, and bilingual language model were the input to the Start Synchronous Decoder to produce the most probable out. The recognizer achieved a 51% WER for English and 89% WER for Filipino. If there are more properly segmented data from different speakers coupled with a well designed Language Model, the accuracy of the recognizer will increase significantly.